Social Cognition : Understanding People and Events - Hamilton, David L. (SAGE Publications, Ltd. (UK), 2020)
Social cognition is an approach to understanding how people think about people and events. We are constantly processing information to navigate the world we live in. The authors will guide your students, using examples and up-to-date studies, through this approach; from explaining the processes themselves right through to demonstrating the role cognitive processes play in our social lives. With chapters on the following processes: ·       Memory ·       Judgement ·       Attention ·       Attribution ·       Evaluation ·       Automatic processing. This book will provide your students with a framework for understanding the most common areas of interest for Social Cognition, such as perception, attitudes and stereotyping.